Is There A Synergy in Adoption of Climate Smart Agricultural Practices? Evidences from Ethiopia - Tamirat Girma Feyisa (Turkish Journal of Agriculture: Food Science and Technology)
This study assessed the intensity of adoption of climate-smart agricultural practices (CSA), identified determinants of the adoption, and examined adoption synergies and trade-offs among the practices in Ethiopia. The study used cross-sectional data collected by the Ethiopian Central Statistical Agency with the support of the World Bank in 2018/2019. The analysis was done using descriptive statistics and multivariate probit model. Widely promoted CSA technologies i.e. conservation tillage, manure, crop residues, compost, and soil and water conservation practices were considered in the study. The study found soil and water conservation practices were the most widely adopted technologies (77% of farmers) followed by manure application (56% of farmers), and residue cover (54% of farmers). Among the adopters, 43% and 13% of them used conservation tillage and applied compost on their farms respectively. Area-based intensity of adoption of soil and water conservation practices, residue cover, conservation tillage, manure, and compost were 63%, 25%, 18%, 14% and 3%, respectively. The study indicated improvements in government services such as extension, credit, market and watershed programs enhance adoption of CSA practices. Adoption of manure and compost, residue cover and compost, and residue cover and conservation tillage had a positive and significant correlation, implying that adopting one practice increases the likelihood of adoption of the other practice for the same farmer. In conclusion, the government needs to use the opportunity of complementarity effect among adoption decision of the practices and work on driving factors identified to enhance the adoption and build resilient agriculture.